Importance of Control and Evaluation in Ecuadorian Public Management - Morillo-Acosta, Liliana del Carmen (2020)
This study was performed with an interpretive approach within the framework of a qualitative methodology. The purpose of this study is to establish the importance of the control and the evaluation of public management as tools that help improve the performance of public institutions in their constant challenge of eradicating the mismanagement of public resources and promoting the accomplishment of the goals set in the government agendas. The literature review along with the analysis of the Ecuadorian experience around corruption emphasizes that the efficiency of the processes is sustained on the control systems established on the basis of the organizational values and evidenced in the transparency of the accountability. As a result of this evaluation, proposals for change and improvement of public policies, programs, and projects are presented. The constitutional amendments to articles 211 and 212 approved in December 2015, eliminating the Ecuadorian State Comptroller General competencies to perform assessments on the state bureaucracy and the achievement of in-stitutional objectives, were abolished in May 2018. As a result of this analysis, it is concluded that, the control and the evaluation are determining factors in the strengthening and consolidation of institutional development processes. The recommendations made as a result of the implementation in the control and evaluation, contribute to the formulation of public policies and the democratization of management.